Critical Analysis of the Education Reforms undertaken since 1990 in Research Teachers in Metropolitan Lima - Oscco Solórzano, Rolando (2019)
The objective of this research was to generate a theory about the Neoliberal Education Reform, undertaken since 1990 and developed with different aspects in the governmental periods, from Fujimori to Ollanta Humala. This study was developed within the qualitative paradigm, with grounded theory methodology and description of the phenomenal situation. The sample consisted of six informants, who provided the data through the in-depth interview technique. As a result, it was found that there was no explanatory theory that reveals the background of this Education Reform as well as teachers who do not identify with this reform, the successes and failures of it. The contributions broaden the reflexive theoretical universe of society, which has to do with Peruvian education.